Analyzing the complexity of Identity in a Multilingual Society Chimamanda Ngouzi Adichie Half of a Yellow Sun (2007) - KOUIDRI, Salma; BEDERINA, Sarra Ahlam (Faculty of Letters and Foreign Languages Department of English, 2019)
The use of the colonizer’s language by the postcolonial African writers was behind the debate among the African writers as far as this work is concerned. African writings have been questioned for it has been written in the language of the colonizer and not in the African languages. The main purpose of this research is to shed light on the issues of identity and language in postcolonial African writing employed by Chimamanda Ngouzi Adichie in her novel Half of a Yellow Sun (2007). Therefore, it seeks to examine the effects the complexity of identity throughout the novel’s major characters under the influence of the colonial education and it emphasizes also on the shaping of the African identity under the influence of a multilingual society through Adichie’s characters. Accordingly, discusses the causes that led to the African writer relies on the colonizer’s language while questioning for the African identity using the new literary style which is the creation of the postcolonial African writer . This dissertation detected a real presentation of the African experience through an African voice.